Investigação do potencial senoterapêutico das N-benzoiltiraminas de Aniba riparia em modelo de senescência endotelial induzida por D-galactose e por abordagens in sílico - Pontes, Larisse Virgolino da Silva (2024)
Biological aging is a time-related protection of molecular, cellular, and tissue physiological functions. During the process, there is an accumulation of senescent cells in the body, making the individual more susceptible to diseases, such as cardiovascular disease (CVD), the leading cause of morbidity and mortality worldwide. The endothelium, the inner layer that lines the blood vessels, is susceptible to this specific condition and, when dysfunctional, causes negative changes in the functioning of the cardiovascular system. On the other hand, senotherapeutic tools can delay damage caused by aging. Therefore, there is an urgent need to search for new drug candidates capable of mitigating the damage caused by aging. Riparins, molecules extracted from the species native to the Amazon region Aniba riparia (Nees) Mez, have already demonstrated significant anti-inflammatory and antioxidant effects in non-clinical studies, critical mechanisms for attenuating cellular senescence. Therefore, this work aimed to investigate the potential chemotherapeutic effect of four analogs of N-benzoyltyramines from Aniba riparia (Nees) Mez in an in vitro endothelial aging model and characterize potential targets for their pharmacological action in silico. For this, rat aortic endothelial cells (RAECs) were cultured, and D-(+)-galactose (Dgal) was used as a senescence inducer. Initially, a triple screening for anti-senescent action (SA-β-Gal), cellular planning (MTT), and antioxidant action (DHE) was carried out for the four riparins. These tests took place in two experimental situations: basal condition and in an endothelial senescence model. Only riparin III was able to improve cellular improvement in the model condition. Furthermore, riparins I, III, and IV were able to reduce senility levels and improve oxidative stress. Another important finding was that only riparin II promoted reduced cellular radiation and increased senescence levels in the basal condition, demonstrating an exclusion effect at the concentrations tested. Riparin III improved cellular prediction in the basal condition, indicative of greater attention or improvement in cellular metabolism. Furthermore, riparins I and III showed antioxidant activity in the basal condition. Prospecting in vivo tests, the pharmacokinetic profile of riparins was investigated, showing them to be good candidates. Furthermore, in search of targets for the mechanism of action, we selected riparin I and protein systems involved in cellular senescence pathways such as Nrf-2/Keap1, MAPK, p38, mTOR, NADPH oxidase, Nf-κB, Sirtuin 1 and 5, to realize molecular protection. Taken together, the results revealed the ability of riparin to bind in an energetically favorable manner to targets selected in the in silica approach, related to antioxidant and anti-senescent pathways (NADPH oxidase, Nf-κB and Sirtuin 5), prospecting a possible mechanism of action for the effects found.